The role of periodontal regeneration in the management of advanced periodontal defects. Series of case reports - Kamil, Wisam Alaa; Hussin, Akbar Sham; Hassan, Haszelini; Wan Hamat, Wan Azila; Mohamed Ali, Suhaila (2015)
Introduction: High prevalence of periodontitis has been reported in the 21st century. However, the traditional nonsurgical periodontal treatment results in healing by long junctional epithelium. Long-term stability of the teeth requires reconstruction of what have been lost from the soft and hard tissues of the periodontium. Case report: Clinical selection of 4 cases characterised by advanced periodontal defects were selected for this report. Case I, advanced bone loss at distal site of tooth 11 with pus discharge was presented with a history of root perforation during RCT. Case II, severe circumferential bone defect around teeth 11 and 21 with pus discharge and grade II mobility. Significant bone gain and pocket depth reduction were achieved and maintained for both cases at 12 and 6 months respectively after applying bone replacement xenograft and collagen barrier membrane. Case III, implant placement in a narrow ridge width at the extraction site of tooth 44 resulted in alveolar crestal bone dehiscence at the buccal aspect. Case IV, severe bone resorption in the buccal plate due to previous extraction of tooth 12 contraindicates direct implant placement. Substantial bone thickness was recorded in both cases as observed in CBCT 12 months post surgical regenerative treatment providing adequate support for dental implant. Conclusion: Since patients prefer the option of maintaining their teeth over extraction and replacement by dental implants compared to dentures, the regenerative periodontal therapy would offer promising potential for successful periodontal reconstruction even in advanced periodontal defects.